Determination of the biological activities of the components present in the venom from the endemic Ecuadorian scorpion Teuthraustes aff. atramentarius - Flores Naranjo, Eddy Mateo (2020)
Ecuador, in spite of its small land area, harbors a great diversity of scorpion species. Most of the endemic Ecuadorian scorpions have an abundant presence within the big cities. The endemic scorpion species Teuthraustes aff. atramentarius is largely distributed in the Andean region and has a great presence in the metropolitan area of Quito. The significant interaction of these scorpions with humans and their activities may lead to accidental stings. There is no information on the toxicity and biological activities of the venom of any species of scorpions in the country. This study describes the biological activity of the components present in the venom of the Ecuadorian endemic scorpion Teuthraustes aff. atramentarius. The venom was fractionated by Reversed-Phase High-Performance Liquid Chromatography, and the molecular weights of the separated components were determined by mass spectrometry. Separated components were tested to determine their enzymatic, antibacterial, and toxic activities. The venom of Teuthraustes aff. atramentarius presented hyaluronidase activity, and several fractions showed toxicity against insects. The venom did not present any antibacterial properties against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli strains. One of the toxic components was sequenced, and its amino acid sequence has similarities with an insecticidal component isolated from the African scorpion Hadogenes troglodytes.